Pengaruh Model Argument-Driven Inquiry Terintegrasi STEM terhadap Pengembangan Argumentasi Ilmiah di Sekolah Menengah Indonesia - Neni Hasnunidah; Nadya Meriza; Sherly Fadhila; Undang Rosidin (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the effectiveness of integrating Argument-Driven Inquiry (ADI) with Science, Technology, Engineering, and Mathematics (STEM) education to improve high school students' argumentation skills on the topic of the human respiratory system. This study was conducted at MTs Negeri 2 North Lampung, using a quasi-experimental design with a non-equivalent group design. The population consisted of 166 students spread across five different classes. From this population, samples were taken, namely students in class VIII 1 as the experimental group and students in class VIII 3 as the control group, through a cluster random sampling technique. The research instrument was a 10-question essay test that had been validated to assess students' argumentation skills. The N-Gain data of the argumentation skills of both classes were shown to be normally distributed. Based on the homogeneity of the data obtained, both had homogeneous variances. Data were analyzed using an Independent Samples t-test and effect size calculation. The results showed that the experimental class achieved a significantly higher increase in argumentation skills compared to the control class (0.46 vs. 0.29, p < 0.05). The large effect size (1.26) confirmed the model's substantial impact. Student feedback was overwhelmingly positive (82.50%). Based on the evidence, it can be concluded that the ADI-STEM learning model effectively improves students' argumentation skills and fosters 21st-century skills by aligning scientific practices with interdisciplinary learning.